An In-depth Analysis of Cyberattacks and Cybersecurity: New Trends and Advancements - Deepak Kumar Sharma; Tejinder Pal Singh Brar (International Journal of Information Security Engineering, 2025)
At present, a significant portion of global economic, commercial, cultural, social, and governmental activities and interactions, including those involving individuals, NGOs, and state institutions, takes place in cyberspace. In recent times, many businesses and government agencies around the world have been facing the growing challenge of cyberattacks and the risks associated with wireless communication technologies. As modern society becomes increasingly dependent on digital technologies, protecting sensitive information from cyber threats has become a major concern. The primary aim of cyberattacks is often to cause financial harm to organizations, although in some cases, they may also pursue military or political objectives. This study aims to explore and critically assess the current developments in the field of cybersecurity, while also identifying the challenges, weaknesses, and advantages of the proposed approaches. A variety of novel descendant assaults are examined in depth. Standard security frameworks are examined alongside the historical context and early-generation cybersecurity methodologies. Additionally, developing trends and current breakthroughs in cybersecurity, along with associated dangers and difficulties, are addressed. The thorough review study given for IT and cybersecurity researchers is anticipated to be beneficial.
Keywords: Cyber security; cyber warfare; cybercrime; security; threats